2022
DOI: 10.1161/jaha.122.024675
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Aortic Atherosclerosis in Adolescents With Chronic Disease

Abstract: Background Adolescents with chronic disease are often exposed to inflammatory, metabolic, and hemodynamic risk factors for early atherosclerosis. Since postmortem studies have shown that atherogenesis starts in the aorta, the CDACD (Cardiovascular Disease in Adolescents with Chronic Disease) study investigated preclinical aortic atherosclerosis in these adolescents. Methods and Results The cross‐sectional CDACD study enrolled 114 adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…In the cross-sectional CDACD study, 114 adolescents aged 12–18 were prospectively enrolled between April 2017 and June 2019, as recently published [2] . The study population included patients with metabolic, inflammatory, and hemodynamic disorders: cystic fibrosis (CF, n = 24), corrected coarctation of the aorta (CoA, n = 25), rheumatoid factor negative polyarticular or extended oligoarticular juvenile idiopathic arthritis (JIA, n = 20), obesity (n = 20), and as a control group healthy adolescents with a corrected atrial septal defect (ASD), who showed normal cardiac dimensions and functions during follow-up (n = 25).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the cross-sectional CDACD study, 114 adolescents aged 12–18 were prospectively enrolled between April 2017 and June 2019, as recently published [2] . The study population included patients with metabolic, inflammatory, and hemodynamic disorders: cystic fibrosis (CF, n = 24), corrected coarctation of the aorta (CoA, n = 25), rheumatoid factor negative polyarticular or extended oligoarticular juvenile idiopathic arthritis (JIA, n = 20), obesity (n = 20), and as a control group healthy adolescents with a corrected atrial septal defect (ASD), who showed normal cardiac dimensions and functions during follow-up (n = 25).…”
Section: Methodsmentioning
confidence: 99%
“…Waist and hip circumference were measured following established clinical standards [2] . Blood pressure was measured three times at the right arm after 10 min rest while seated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, there are conflicting data regarding the utilization of cIMT in the pediatric population. Ilisson et al [ 26 ] found increased cIMT in children at the early stage of JIA, whereas Mani et al [ 27 ] and Ververs et al [ 28 ] did not observe any significant difference between JIA patients and healthy controls. There are no data on cIMT values in healthy children depending on their attitude to the rules of cardiovascular prevention.…”
Section: Introductionmentioning
confidence: 99%